Influence of convenience, trust, and lifestyle on Islamic consumption behavior among millennials: A study on Shopeepay Later users - Fitriyani, Arum Teguh; Bawono, Anton (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2023)
Technological advancements have transformed cellphones into multifunctional tools, significantly increasing internet usage in Indonesia. This study examines the impact of convenience, trust, and lifestyle on Islamic consumption behavior among millennials using Shopeepay Later. Utilizing a quantitative approach, data was collected via online questionnaires from 50 respondents in Semarang Regency. Multiple regression analysis was employed to evaluate the hypotheses. Findings reveal that lifestyle significantly influences Islamic consumption behavior, while convenience and trust do not have notable individual impacts but do collectively affect behavior. The study underscores the importance of integrating ethical education with financial literacy to foster responsible consumption aligned with Islamic values. These insights contribute to understanding how modern financial practices intersect with traditional ethical frameworks, offering valuable implications for policymakers and financial service providers aiming to promote balanced and ethical consumption practices among millennials.